Do professor de literatura ao formador de leitores críticos de textos literários: um estudo sobre a (re)invenção do professor de língua portuguesa para otrabalho com a leitura literária no novo Ensino Médio. - Rodrigo Alves dos Santos (2009)
The current paper consists of a study that works with a parcel of the discourse which aims to adjust and arrange the education and the professional performing of the Portuguese teacher, regarding to the desired work with literary reading towards, what has been called, the novo Ensino Médio (new Secondary School). This research, based on Michel Foucault theories and on foucaultian studies, considers thediscourse on what it produces, and takes for granted the fact that the teacher is a discursive construction, traversed by discourses that materialize into documents which have the purpose of adjust and arrange the academic degree of the teachers that are already (and/or will be) in the formal Brazilian education classrooms. Considering these previous statements, a discourse analysis is developed through a published discursive materiality which contains the following documents: 1)Parâmetros Curriculares Nacionais de Língua Portuguesa do Ensino Médio (1999) (Secondary Education National Curriculum Parameters of the Portuguese language - 1999), 2) PCN+ (Complementary teaching orientation in the National Curriculum Parameters) of the Portuguese language, for the same level (2002), 3) Orientações Curriculares do Ensino Médio de Língua Portuguesa (2006), (The Portuguese language area in Secondary Education Curriculum Orientation - 2006)), 4) PlanoNacional de Educação (PNE 2001) (The Educational National Plan (ENP 2001)), 5) the CNE/CP 1 and CNE/CP 2 resolutions, published at the Official Diary of the Union on April 09th 2002 (that approach the regulation of the teachers academic courses for basic education), 6) Diretrizes Curriculares Nacionais do Curso de Letras (National Curriculum Directives for Letras Course), published under the CNE/CES2001 judgment, at the Official Diary of the Union 07/09/2001, 7) Political-pedagogic projects of two Portuguese language courses (the Letras course from the Federal University of Minas Gerais and from the Federal University of Viçosa). The discourse published in all these materiality is questioned underlying in elements like the enunciation analysis and the foucaultian genealogy about the way these documents are creating and demanding from the attitudes of the Portuguese teacherthat works with the literary reading with the secondary school. This study certifies that the statement that describes the teacher as the principle changer of the formal education it is the most recurrent among the discourse analyzed. Therefore, the teacher, demanded and created by the discourse, is the responsible for the development of critical literary texts readers, which means, according to this research, the death of the Literature teacher among the basic education. By the creation of this other Portuguese teacher in the development of the literary reading, and according to the emergency noticed in the discourse analyzed throughout this paper, its possible to observe a new way of existence coming up, where people that want to work as Portuguese teachers, in the last grades of the basic education, must fill out the forms.